(3R, 3'R)-zeaxanthin protects the retina from photo-oxidative damage via modulating the inflammation and visual health molecular markers - Şahin, Kazım; Akdemir, Fatih; Orhan, Cemal; Tuzcu, Mehmet; Gencoglu, Hasan; Şahin, Nurhan; Juturu, Vijaya (Taylor & Francis Ltd, 2019)
Purpose: Zeaxanthin protects the macula from ocular damage due to light or radiation by scavenging harmful reactive oxygen species. In the present study, zeaxanthin product (OmniXan (R); OMX), derived from paprika pods (Capsicum annum; Family-Solanaceae), was tested for its efficacy in the rat retina against photooxidation. Methods: Forty-two male 8-week-old Wistar rats exposed to 12L/12D, 16L/8D and 24L/0D hours of intense light conditions were orally administrated either 0 or 100 mg/kg BW of zeaxanthin concentration. Retinal morphology was analyzed by histopathology, and target gene expressions were detected with real-time polymerase chain reaction methods. Results: OMX treatment significantly increased the serum zeaxanthin concentration (p < 0.001) and ameliorated oxidative damage by increasing the antioxidant enzyme activities in the retina induced by light (p < 0.001). OMX administration significantly upregulated the expression of genes, including Rhodopsin (Rho), Rod arrestin (SAG), G alpha Transducin 1 (GNAT-1), neural cell adhesion molecule (NCAM), growth-associated protein 43 (GAP43), nuclear factor-(erythroid-derived 2)-like 2 (Nrf2) and heme oxygenase (HO-1) and decreased the expression of nuclear factor-kappa B (NF- kappa B) and GFAP by OMX treatment rats. The histologic findings confirmed the antioxidant and gene expression data. Conclusions: This study suggests that OMX is a potent substance that can be used to protect photoreceptor cell degeneration in the retina exposed to intense light.
Keywords: Light-emitting diode (LED); oxidative stress; photo-oxidation; retina; zeaxanthin